(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
This study aims to try to improve the production and quality of laying hens’ eggs in the late stages of their productive life by adding some herbal plants to the fodder. 288 laying hens at 64 weeks old were used and it was distributed into four treatments, with three replicates for each treatment, and each replicate had 24 laying hens. The first treatment was a control free of the addition, The second treatment included adding 1% of rosemary, the third treatment included adding 2% of thyme, and the fourth treatment adding 1% of garlic. The statistical analysis results showed that there was a significant superiority of the rosemary treatment in the average egg weight, while the thyme addition treatment was superior in the average egg mass, feed conversion factor, and egg production percentage. The additives also led to an increase in feed consumption compared to the control treatment